Strategi Peningkatan Kinerja Rantai PasokanIkan Tribang(Upeneus moluccensis) dari Pasar Lelang IkanGunung Agung Sampai Konsumen Rumah Tangga Kota Denpasar - I Gusti Putu Angga Wira Dananjaya; I Wayan Widia; Ida Ayu Rina Pratiwi Pudja (Jurnal BETA (Biosistem dan Teknik Pertanian), 2019)
Supply chain system of tribang fish currently does not provide welfare to people business, especially small traders. The purpose of this study are (1) to know the structure, mechanism, and institutional supply chain of tribang fish; (2) find strategic steps to improve the performance of tribang fish supply chains. This study consisted of two stages, the first stage knowing the structure, mechanism, institutional supply chain using qualitative descriptive analysis, and the second stage knowing the priority recommendations using the Analitycal Hierarchy Process (AHP) method. Sampling of supply chain actors uses purposive sampling, snowball sampling, and non probability sampling methods. The results showed that tribang fish supply chain consisted of nine chain flow patterns where the tribang fish supply chain mechanism was traditional and the tribang fish supply chain institution was general trading. Based on AHP method, priority recommendations to improving the performance of tribang fish supply chains are criteria of increasing product added value, alternative of responsiveness (supply chain reaction capabilities), and indicator of cycle order fulfillment are the most important priorities.